Direct Probing of Grain Boundary Resistance in Chemical Vapor Deposition‐Grown Monolayer MoS2 by Conductive Atomic Force Microscopy. Issue 2 (4th September 2019) - Giannazzo, Filippo; Bosi, Matteo; Fabbri, Filippo; Schilirò, Emanuela; Greco, Giuseppe; Roccaforte, Fabrizio
Abstract : Grain boundaries (GBs) of transition metal dichalcogenide monolayers (MLs) play an important role in many charge transport phenomena observed in 2D materials. Herein, nanoscale resolution current mapping by conductive atomic force microscopy (CAFM) is used for direct probing of the resistance associated with GBs in ML MoS2 grown by chemical vapor deposition (CVD) onto a SiO2 /Si substrate. Local current–voltage ( I–V ) characteristics acquired within individual adjacent MoS2 domains allow extracting the metal/MoS2 Schottky barrier height (ΦB ≈ 0.3 eV), as well as the intradomains and GB resistance contributions. The high value of GB resistance (≈6 times the value measured on an individual domain) can be responsible, in part, for the low field‐effect mobility ( μ ≈ 0.12 cm 2 V −1 s −1 ) measured on back‐gated ML CVD MoS2 field‐effect transistors. Abstract : Nanoscale resolution current mapping and local current–voltage analyses by conductive atomic force microscopy (CAFM) are used to evaluate the resistance associated with individual domains and grain boundaries in polycrystalline monolayer MoS2 grown by chemical vapor deposition (CVD) on a SiO2 substrate.